Perancangan Jaringan Backhaul Sistem Transmisi Gelombang Mikro Digital Menggunakan Frequency Diversity dan Tanpa Diversity di Wilayah Kepulauan Riau - Yosy Yosy Rahmawati; Ade Wahyudin (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2018)
The progress of information and communication technology has resulted in a number of villages in Lingga Regency, Riau Islands still feeling the lack of public information due to signal limitations. One of the islands in the spotlight of the government is Pekajang Island. Economically the population of Pekajang Island interacts more with Bangka Island. A considerable distance and very minimal transportation facilities make Pekajang Island isolated. Therefore, to provide ICT services, a backhaul network is needed to support access to ICT services. In the study, a backhaul network of microwave transmission systems has been designed using frequency and diversity without diversity in the Riau archipelago. From the results of the design test using Pathloss 5.0 Simulator, the reliability value of the system that uses frequency diversity is 99.96879% and without diversity is 99.81417%. It can be concluded that the design results of a microwave transmission system using frequency diveristy are feasible to be applied because it has a system reliability value above the threshold based on ITU-R G.827 and F.1703 standards.Perancangan Jaringan Backhaul Sistem Transmisi Gelombang Mikro Digital Menggunakan Frequency Diversity dan Tanpa Diversity di Wilayah Kepulauan Riau